FASN inhibition sensitizes metastatic OSCC cells to cisplatin and paclitaxel by downregulating cyclin B1. (29th September 2021) - Almeida, Luciana Yamamoto de; Moreira, Fernanda dos Santos; Santos, Guilherme Augusto Silva dos; Cuadra Zelaya, Florence Juana Maria; Ortiz, César Alexander; Agostini, Michelle; Mariano, Flávia Sammartino; Bastos, Débora Campanella; Daher, Ulisses Ribaldo Nicolau; Kowalski, Luiz Paulo; Coletta, Ricardo D.; Graner, Edgard
Abstract: Objectives: To investigate the potential effect of fatty acid synthase (FASN) inhibitor orlistat to enhance the effectiveness of chemotherapy drugs widely used to treat oral squamous cell carcinomas (OSCC), such as 5‐fluorouracil, cisplatin, and paclitaxel. Methods: The OSCC SCC‐9 LN‐1 metastatic cell line, which expresses high levels of FASN, was used for drug combination experiments. Cell viability was analyzed by crystal violet staining and automatic cell counting. Apoptosis and cell cycle were analyzed by flow cytometry with Annexin‐V/7‐AAD and propidium iodide staining, respectively. Cyclin B1, Cdc25C, Cdk1, FASN, and ERBB2 levels were assessed by Western blotting. Finally, cell scratch and transwell assays were performed to assess cell migration and invasion. Results: Inhibition of FASN with orlistat sensitized SCC‐9 LN‐1 cells to the cytotoxic effects of paclitaxel and cisplatin, but not 5‐fluorouracil, which was accompanied by a significant reduction in cyclin B1. The suppression of proliferation, migration, and invasion of SCC‐9 LN‐1 cells induced by orlistat plus cisplatin or paclitaxel was not superior to the effects of chemotherapy drugs alone. Conclusion: Our results suggest that orlistat enhances the chemosensitivity of SCC‐9 LN‐1 cells to cisplatin and paclitaxel by downregulating cyclin B1.